PERBANDINGAN EFEKTIVITAS DOSIS PUPUK NPK BOOSTER DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN SERTA PRODUKTIVITAS TANAMAN MELON GOLDEN (Cucumis melo L.) - Doni Hermawan Dwi Yulianto; Maylani Lucky (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
This study aimed to determine the optimal combination of NPK Booster fertilizer dosage and manure ratio for the growth and yield of Golden Melon. The research was conducted in Sekadau Hilir District, Sekadau Regency, West Kalimantan, from September 2024 to December 2024. A completely randomized design (CRD) with a factorial pattern was used, involving two factors. The first factor was the NPK fertilizer dosage, consisting of three levels: N1 (10 grams), N2 (12.5 grams), and N3 (15 grams). The second factor was the ratio of soil to chicken manure, also in three levels: T1 (2:1), T2 (3:1), and T3 (4:1). Each treatment combination was replicated three times, with three plant samples per replication, resulting in a total of 81 plants. Data from the observed variables were statistically analyzed using Analysis of Variance (ANOVA). If the F-value indicated a significant effect, the analysis was followed by Duncan’s Multiple Range Test at the 5% significance level. The results showed that the combination of NPK Booster dosage and soil-to-manure ratio influenced melon plant growth. A dosage of 15 grams of NPK Booster produced the most effective results in shoot fresh weight, root fresh weight, and individual fruit weight.